Analisa pola hidup sehat masyarakat dalam pemanfaatan MCK di desa Saumanganya Kecamatan Pagai Utara Kepulauan Mentawai - Dian Wahyoni Dewi Fitri; Merry Thressia (EcoNews, 2022)
Saumanganya is the name of a village located in North Pagai District, Mentawai Islands Regency. Saumanganya Village is included in the red zone in the application of the Clean and Healthy Lifestyle (PHBS), especially in the application of the local household environmental waste management system (on site system) individually. On the other hand, there are still many people who do not have waste water management and dispose of their waste directly into rivers, gardens and the sea. In this case, community participation is very much needed in local wastewater management, because the community also plays an active role in producing wastewater. The diverse characteristics of the community will greatly affect the behavior of the community in waste water management. This is closely related to the improvement of public health status. This community activity has the potential to cause environmental pollution, where the main waste comes from households. With a population of 4,141 people consisting of 1,070 houses from 1,082 families. Based on data from the environmental health program in 2021, in Saumanganya Village 15% of the residents still use open defecation (BABS) facilities and the rest are latrine facilities. Seeing this condition, it is appropriate to conduct research that aims to analyze the factors that influence the lifestyle of the people in Saumanganya Village in the application of healthy MCK in accordance with health standards. From the analysis of the lifestyle of the people of Saumanganya Village, it was found that 100% of the people who use MCK according to health standards have not been met due to economic factors 69%, knowledge factors 15%, and 26% are culture/traditions, and 26% lack of education and counseling. about PHBS.